ASSESSMENT OF RUNWAY EXCURSION CAUSAL FACTORS AND MITIGATION STRATEGIES (Nigerian Journal of Technology, 2018)
Runway excursion (RE) is a significant cause of many aircraft accidents worldwide. Statistic reveals that accident associated with RE is on the increase. Although RE accident fatalities are usually lower with respect to loss of control (LOC) caused accidents, however the aircrafts involved in RE caused accidents are usually write-off. In response to the raising threat to aviation safety, the Research and Development (R&D) division of the Air Force Institute of Technology (AFIT), Nigerian Air Force (NAF) Base, Kaduna Nigeria was tasked to conduct a study on RE problem. The study gathered of three kinds of secondary information associated with RE accidents: 1) statistical summaries, 2) accident report that cited runway excursion accident and 3) stakeholders inputs. Using this resources, the RE causal factors were identified. This paper described the study method, stakeholder viewpoint; key identified causal factors for RE caused accidents and mitigation strategies. http://dx.doi.org/10.4314/njt.v37i3.9